Rapid-format recombinant antibody-based methods for the diagnosis of Clostridioides difficile infection: Recent advances and perspectives - Raeisi, Hamideh; Azimirad, Masoumeh; Asadzadeh Aghdaei, Hamid; Yadegar, Abbas; Zali, Mohammad Reza (Frontiers in Microbiology, 2022)
Clostridioides difficile, the most common cause of nosocomial diarrhea, has been continuously reported as a worldwide problem in healthcare settings. Additionally, the emergence of hypervirulent strains of C. difficile has always been a critical concern and led to continuous efforts to develop more accurate diagnostic methods for detection of this recalcitrant pathogen. Currently, the diagnosis of C. difficile infection (CDI) is based on clinical manifestations and laboratory tests for detecting the bacterium and/or its toxins, which exhibit varied sensitivity and specificity. In this regard, development of rapid diagnostic techniques based on antibodies has demonstrated promising results in both research and clinical environments. Recently, application of recombinant antibody (rAb) technologies like phage display has provided a faster and more cost-effective approach for antibody production. The application of rAbs for developing ultrasensitive diagnostic tools ranging from immunoassays to immunosensors, has allowed the researchers to introduce new platforms with high sensitivity and specificity. Additionally, DNA encoding antibodies are directly accessible in these approaches, which enables the application of antibody engineering to increase their sensitivity and specificity. Here, we review the latest studies about the antibody-based ultrasensitive diagnostic platforms for detection of C. difficile bacteria, with an emphasis on rAb technologies.